Routledge companion to world literature - D'haen, Theo; Damrosch, David; Kadir, Djelal (London Routledge, 2023)
"This fully updated new edition of The Routledge Companion to World Literature contains 10 brand new essays on topics such as Premodern World Literature, Migration Studies, World History, Artificial Intelligence, Global Englishes, Remediation, Crime Fiction, Lusophone literature, Middle Eastern literature, and Oceanic Studies"--
Part one. The historical dimension -- Part two. The disciplinary dimension -- Part three. The theoretical dimension -- Part four. The geographical dimension.
Includes bibliographical references and index.
Keywords: Literature; Literature and society; Literature and globalization